Identifying glyphosate-tolerant maize by soaking seeds in glyphosate solution - Shu-feng YAN; Sher Muhammad; Hai-fang LIU; Shuang-gui TIE; Shu-ku SUN (Journal of Integrative Agriculture)
The identification of glyphosate-tolerant maize genotypes by field spraying with glyphosate is time-consuming, costly and requires treatment of a large area. We report a potentially better technique of seed-soaking to identify glyphosate-tolerant maize genotypes. The effects of soaking maize seeds in glyphosate solution under controlled conditions were studied on seed germination rate, seedling morphological indices, seedling growth and leaf chlorophyll content. These responses were compared among a glyphosate-tolerant transgenic maize cultivar CC-2, glyphosate-susceptible inbred line Zheng 58 (the recurrent parent of CC-2) and hybrid cultivar Zhengdan 1002. The results showed that the germination rate, seedling morphological indices and leaf chlorophyll content of glyphosate-tolerant CC-2 seeds did not change significantly among five different concentrations of glyphosate treatment (0 to 2%). In contrast, germination rates, seedling morphological indices and leaf chlorophyll contents of Zheng 58 and Zhengdan 1002 seeds were significantly negatively affected by exposure to increasing concentrations of glyphosate. The glyphosate-tolerant inbred line CC-2 displayed a strong tolerance to glyphosate after soaking in 0.1 to 2.0% glyphosate solutions, while both the inbred line Zheng 58 and hybrid Zhengdan 1002 were susceptible to glyphosate. The accuracy of the glyphosate-soaking method for screening glyphosate-tolerant maize was confirmed using a field spraying trial.